Análisis comparativo del potencial de licuación evaluado por métodos semiempíricos spt y cpt (2019)
As a contribution to the study of the phenomenon of liquefaction in granular soils originated by the occurrence of seismic events, a comparative analysis of the safety factors against cyclic lique-faction, obtained from the standard penetration field tests and penetration with piezocones, was carried out. Places with different levels of acceleration in rock were studied and with information available from these field tests, specialized software was used for analysis and it was concluded, about the behavior of the safety factor against cyclic liquefaction with respect to the type of test, that there is no correspondence between the two tests and that, in application of the principle of redundancy, it is recommended that the use of these is simultaneous and complementary. It was also concluded that, for the calculation of the liquefiable potential, the piezocone penetration test is more conservative than the standard penetration test and that, with the increase of the acceleration in rock, the comparative differences obtained in the safety factors, calculated with the methodolo-gies accepted by the scientific community for these two trials, are reduced.